The Influence of Teaching at the Right Level (TaRL) Based Learning and Students’ Motivation Levels on Physical Education Learning Outcomes at SMA Negeri 1 Sale Rembang - Ardian Yoga Pangestu; Hermawan Pamot; Ipang Setiawan (Journal of Physical Education and Sports, 2026)
Physical Education learning at the senior high school level faces challenges related to student ability heterogeneity and varying motivation levels, which often result in learning disparities. This study aimed to analyze the effects of Teaching at the Right Level (TaRL)-based learning methods and students' motivation levels on PJOK learning outcomes. A 2×2 factorial experimental design was employed with 140 tenth-grade students from SMA Negeri 1 Sale Rembang divided into four treatment groups. The research implemented two TaRL approaches: TaRL A utilizing peer tutoring strategy and TaRL B utilizing parallel learning strategy. Students were categorized into high motivation (n=72) and low motivation (n=68) groups based on motivation questionnaire scores. Two-way ANOVA analysis revealed a significant main effect of TaRL method on learning outcomes (F=5.098, p=0.026, η²=0.036), with TaRL A demonstrating superior performance (M=78.18) compared to TaRL B (M=74.86). More significantly, students' motivation level demonstrated a very large main effect (F=30.021, p=0.000, η²=0.181), with high-motivation students achieving substantially higher scores (M=80.91) than low-motivation students (M=71.97). No significant interaction was found between method and motivation (F=0.246, p=0.621). These findings indicate that both factors independently contribute to PJOK learning outcomes, with motivation being approximately five times more influential than teaching method. Schools should prioritize implementing peer tutoring-based differentiation while simultaneously enhancing student motivation through autonomy, competence, and relatedness support